Nursing care of the patient before, during, and after transfusion of blood and its components: management principles - Bociąga, Patrycja; Lachowicz, Judyta; Spodymek, Aleksandra (Nursing Problems / Problemy Pielęgniarstwa, 2025)
Approximately 1.7 million transfusions of blood and blood components are performed annually in Poland. The safety of the patient during the transfusion procedure is determined by the cooperation of doctors, nursing staff, and staff of the transfusion immunology laboratory and blood bank, and nurses play a crucial role in this process. The aim of this study is to present the legal and practical aspects of transfusion patient care that nursing staff should be familiar with to ensure the safety and effectiveness of the procedure. The work is based on a review of current knowledge, as well as an analysis of legislation and articles, showing the role of nurses in the transfusion process. It concludes that nurses play a key role in every step of the transfusion process, from patient preparation to the procedure itself and post-transfusion care, providing a crucial link in ensuring patient safety.